The English Democrats Party ou l’émergence d’une nouvelle mouvance : le nationalisme autonomiste anglais - Claude BARBANTI (E-REA)
Devolution at the end of the 1990s has led to numerous consequences and transformations in British politics. The traditional and centralised Westminster system has been turned upside down, and many studies have been carried out on the various aspects of this new “devolved Britain”.Yet, few have paid attention to the English case. However, the constitutional asymmetry thus created has indeed also affected England. When Celtic MPs succeed to influence the outcome of votes on exclusively English matters, one can realise that there is no such thing as an English government. Therefore, some English MPs have felt the need to ask for an option of “English Votes on English Laws”. This article tries to demonstrate that a feeling of “resentment” emerges from this situation and leads to the birth of a new “English” nationalism, entirely dedicated to obtaining an English Parliament.